Gut microbiome and blood glucose control in type 1 diabetes: a systematic review - Abuqwider, Jumana; Corrado, Alessandra; Scidà, Giuseppe; Lupoli, Roberta; Costabile, Giuseppina; Mauriello, Gianluigi; Bozzetto, Lutgarda (Frontiers in Endocrinology, 2023)
The risk of developing micro-and macrovascular complications is higher for individuals with type 1 diabetes (T1D). Numerous studies have indicated variations in gut microbial composition between healthy individuals and those with T1D. These changes in the gut ecosystem may lead to inflammation, modifications in intestinal permeability, and alterations in metabolites. Such effects can collectively impact the metabolic regulation system, thereby influencing blood glucose control. This review aims to explore the relationship between the gut microbiome, inflammation, and blood glucose parameters in patients with T1D.